Determining the force of the kick at the ball and muscle sensitiveness of young football players - Girdauskas, G.; Kazakevicius, R. (Education. Physical training. Sport, 1999)
The search for gifted athletes, their selection and improving the methods of training are the most urgent problems in modern sport. Football is one of the kinds of sports in which the purposeful training of football players is getting increasingly younger in years. It becomes obligatory therefore to start searching for new forms of improving the training of young football players as early in age as possible. The aim of our study was to determine the force of the kick at the ball of 11-16 years old football players as well as the sensitiveness of their leg muscles, i. e. muscle guadriceps femoris, muscle biceps femoris, muscle tibialis anterior and muscle gastrocnenius, by means of a specially devised apparatus. After the research was carried out it has been determined that the force of kick at the ball of young footballers increases with age while the sensitiveness of leg muscles when performing kick at the ball is different considerably in different age groups. The greatest force of the kick at the ball and the greatest sensitiveness of leg muscles have been found among the 15 years old football players. It is also evident from the research carried out that the greatest changes in the force of the kick at the ball take place in the group of football players aged 13 and 14 years while the greatest changes in the sensitiveness of leg muscles have been registered in the 12-13 year-old group of young footballers.